Aesthetic appreciation of Kelantan heritage ceramics: an indicator for sustainability - Ab. Aziz Shuaib; Olalere, Folasayo Enoch; Khairul Azhar Mat Daud; Muhamad Ezran Zainal Abdullah; Jafrulhizam Jaafar (2014)
Apart from creating clay objects with unlimited variety of shapes, the surface can also be decorated wi th patterns in many ways to enhance the overall appearance. As a result of this, surface decorations have been one of the major heritage values in ceramic studies. Thus, applying Gestalt theory and Golden section rule, this paper seeks to identify the unique heritage values in Kelantan ceramics that can be sustained as genius loci. Pict orial data (decorative patterns) were collected by visiting si x museums in Kelantan and the data were analyzed wi th the aid of PhiMatrix software. The result shows eleven (11) decorative patterns that conform to the golden sec tion rule and the Gestalt principles of grouping elements. He nce, sustaining this heritage values will not only serve as identity, but also demonstrate the recognition of the beauty of the past